ANALYZING THE RELATIONSHIP OF PERCEIVED ORGANIZATIONAL SUPPORT WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR: EVIDENCE IN THE INDONESIAN GOVERNMENT SECTOR - Nirmala, Isma; Marhaeni, Novie Prasetyaning; Oktisari, Dwi; Waliah, Siti (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
In the Indonesian context, it is important to consider work culture and local values that might influence organizational citizenship behavior. The main aim of the research is to analyze perceived organizational support, organizational commitment, and organizational justice on organizational citizenship behavior. The sample in this research consisted of 150 employees working in the government sector in Indonesia who were determined using a purposive sampling technique approach. Data collection uses a questionnaire instrument which is then distributed online. Data analysis uses the SPSS application by displaying the results of data processing through validity and reliability tests, multiple regression analysis, coefficient of determination and hypothesis testing. Based on the results of data analysis, it is stated that perceived organizational support, organizational commitment, and organizational justice have a positive and significant effect on organizational citizenship behavior. The findings from this study will provide an important contribution in understanding the dynamics of the relationship between organizational support, commitment, and justice on employee proactive behavior, as well as offering recommendations for the development of policies and managerial practices that can increase OCB in the government sectors. Data analysis will be carried out using statistical techniques such as multiple regression to evaluate the influence of these variables simultaneously.